Extracellular vesicles enhance the in vivo antitumor effects of millettia species-derived compounds in chronic myelogenous leukemia therapy - Xie, Zongzhou; Cheng, Xiaozhen; Mao, JianCang; Zhu, Yingqi; Li, Le; Mei, Zhenxin (Frontiers in Chemistry, 2024)
Several Millettia species are being investigated as medicinal ingredients due to their promising anti-cancer and anti-inflammatory properties. However, the application of Millettia species-derived compounds has been severely hindered by their poor aqueous solubility, rapid metabolism, and low bioavailability. Extracellular vesicles (EVs), which as membrane-bound phospholipid vesicle initiatively secreted through a variety of mammalian cells, are increasingly recognized as promising drug delivery vehicles. Therefore, EVs are with great potential to enhance both the stability and efficacy of the Millettia species-derived compounds in treatment. In this study, extracellular vesicles derived from chronic myelogenous leukemia cells are developed for delivering the extracts of Millettia speciosa Champ and Millettia pachyloba Drake-derived Homobutein. Notably, Homobutein-loaded EV (hEV) formed a stable and homogenous nanosized particle with high entrapment efficiency up to 55.7%. Moreover, EVs loaded with Homobutein were significantly more potent than free drugs in inhibiting K562 cell proliferation. The results demonstrated that intravenous injection of EV loaded with Homobutein effectively inhibits tumor growth in tumor-bearing mice compared to free Homobutein. Hence, this strategy can effectively enhance the efficacy of Millettia species-derived drugs in chronic myelogenous leukemia therapy.